Optimization of Edible Straw Characteristics from Kimpul Taro Starch and Patin Fish Skin Gelatin with Sorbitol Addition - Tasya Vyra Putri Ariyani; Amalia Azzahroh; Sintha Soraya Santi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The pervasive contamination resulting from plastic straw usage has necessitated the development of a resolution to address this predicament. One potential avenue for exploration is the development of an environmentally sustainable edible straw. The objective of this study is to design and evaluate the optimal materials and characteristics of an edible straw that complies with the Japanese Industrial Standard, which serves as an international benchmark. The independent variables employed in this study encompass the ratio of kimpul taro starch and catfish skin gelatin, along with sorbitol. These variables were analyzed using Central Composite Design (CCD) and Response Surface Methodology (RSM), with the assistance of Design Expert 13 software. The edible straw was produced through a mixing and casting process, using a ratio of catfish skin gelatin to kimpul taro starch of 5:5; 4:6; 3:7; 2:8; 1:9, along with the addition of plasticizers at varying concentrations of 0%; 0.4%; 0.8%; 1.2%; and 1.6%. The characteristics that were the focus of the analysis included thickness, tensile strength, elongation, solubility, and biodegradation rate. The findings of this study suggest that the edible straw under consideration is in accordance with the Japanese Industrial Standard and is deemed safe for utilization and ingestion.